Sulfur isotope exchange between thiophenes and inorganic sulfur compounds under hydrous pyrolysis conditions. (January 2017) - Meshoulam, Alexander; Amrani, Alon
Highlights: Thermal maturation can enriched model sulfur compounds in 34 S up to ∼2‰. Inorganic sulfur species decrease dramatically the thermal stability of thiophenes. Benzo- and dibenzo-thiophenes do not exchange isotopes with inorganic sulfur species. δ 34 S of BT and DBT are controlled by their relative rates of degradation/formation. Degradation/formation of BTs and DBTs occur during thermal maturation and TSR. Abstract: Sulfur isotope fractionation during thermal degradation of aromatic organic sulfur compounds was studied utilizing quartz tube-hydrous pyrolysis at 360 °C. BT (benzothiophene), DBT (dibenzothiophene), 3-PT (3-phenylthiophene) and 2-OT (2-octylthiophene) were used to represent organic sulfur compounds with a range of thermal stabilities. These compounds were heated for 40 h with and without the addition of reduced inorganic sulfur species: elemental S, sodium sulfide (Na2 S∗9H2 O) and sodium sulfite (Na2 SO3 ). The extent of degradation of each compound showed good correlations with its aromatic stabilization and strongly depended on the added inorganic sulfur species, with DBT being the most stable and 2-OT the least stable. Sulfur isotope enrichments up to 2.2‰ resulted from the thermal degradation of thiophenes. A significant decrease in stability of thiophenes was observed in the presence of reduced sulfur species. In contrast, BT and DBT did not show any exchange of S isotopes with external reduced S pool, while 3-PT did experience S isotope exchange. The results of the present study suggest that the main controls on the δ 34 S values of BT and DBT during TSR are the relative rates of their degradation and their formation from the reaction between TSR-H2 S and petroleum hydrocarbons. This finding improves our confidence in using the δ 34 S of individual thiophenes as reliable proxies for the occurrence and extent of thermal maturation and thermochemical sulfate reduction.